Estimating the Distribution of Air Voids in Concrete - Beasman L.E.; McCuen R.H. (Institute of Research and Community Outreach - Petra Christian University, 2011)
Chord length measurements are used to estimate the volumetric distribution of air voids within hardened concrete samples. The accuracy of the Linear-Traverse method is questionable because chord lengths do not directly represent the actual volumes of the air voids. Using computer simulation, randomly generated concrete samples were analyzed using the Linear-Traverse method to compute the distribution of air voids, the chord length gradation curve, the chord length-to-traverse ratio, and the air void volume gradation curve. The current chord-length approach significantly underestimated the air void content. A method that estimates that air void gradation curve from the chord length gradation curve is presented. The computer simulation results are supported by a conceptual analysis. To obtain the most accurate estimate of the air void content, computer analyses showed that at least 15 traverse lines should be regularly spaced on the concrete sample.